Pemodelan Simulasi dan Perbaikan Metode Kerja Berbasis Eliminate, Combine, Rearrange, And Simplify (ECRS) pada Proses Produksi Hijab - Winnie Septiani; Benediktus Prayoga; Ratna Mira Yojana (Universitas Katolik Parahyangan, 2026)
Konveksi XYZ is an UMKM that produces hijab. This UMKM experiences problems in the form of bottlenecks in the production process. This is characterized by high waiting time between workstations which has an impact on low production efficiency. This study aims to identify the main causes of bottlenecks and design improvements to the production system. The problem is modeled using discrete event-based simulation with ProModel software to describe the actual conditions. The analysis results show that the imbalance of workload between stations and resource limitations in the obras process are the main causes of bottlenecks. Improvements were made using the Eliminate, Combine, Rearrange, and Simplify (ECRS) approach, resulting in proposals to eliminate non-value-added activities, rearrange the location of machines, and redistribute operator tasks. These proposals were simulated again to evaluate system performance. The simulation results showed an increase in efficiency, with a decrease in production time from 7,56 hours to 5,35 hours (29,94% increase in efficiency), as well as a decrease in the average processing time on the obras machine from 8152,24 seconds to 5611,28 seconds, which resulted in an increase in machine utility. Thus, the ECRS approach and ProModel simulation proved effective in overcoming bottlenecks and improving the production performance of UMKM.